Novel approach to synthesize NiCo2S4 composite for high-performance supercapacitor application with different molar ratio of Ni and Co - S. K. Shinde (Nature Portfolio, 2019)
Abstract Here, we developed a new approach to synthesize NiCo2S4 thin films for supercapacitor application using the successive ionic layer adsorption and reaction (SILAR) method on Ni mesh with different molar ratios of Ni and Co precursors. The five different NiCo2S4 electrodes affect the electrochemical performance of the supercapacitor. The NiCo2S4 thin films demonstrate superior supercapacitance performance with a significantly higher specific capacitance of 1427 F g−1 at a scan rate of 20 mV s−1. These results indicate that ternary NiCo2S4 thin films are more effective electrodes compared to binary metal oxides and metal sulfides.